Implementasi Impelmentasi Model Kooperatif Tipe Team Game Turnament dalam Pembelajaran Analisis Nuansa Makna Pada Kumpulan Lagu Letto Band Berdasarkan Majas (Studi Eksperimen di Kelas XII MA Al-Hasaniyah Senori Tuban) - Zulfatun Anisah; Ifah Khadijah; Siti Umi Hanik; Nailly Sa’adatur Rizqiyah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2021)
Analyzing the nuances of the meaning of the song included in the high school curriculum class XII, It indicates that high school students are required to be able to analyze the meaning or interpret the meaning contained in the lyrics of a song poem. However, the reality in the field of learning to analyze the nuances of the meaning of the song is considered difficult for students. Difficulties occur students are less able to master the elements of maje so that the nuances of the meaning of the song cannot be interpreted with the right meaning. The purpose of this study was to determine the effect of analytical learning using the Team Game Turnament (TGT) model on the nuances of the meaning of the song Letto based on the opera, and also to determine the response of students in learning the nuances of the song based on the meaning of the song Letto. This research uses an experimental method. There are two classes studied, namely the experimental class and the control class. Experimental classes that will be subject to treatment get learning with the TGT model. The results showed that learning by applying the TGT model had a positive effect on students' ability to analyze the nuances of the meaning of the Letto song based on majas. Students gave a positive response to learning the nuances of the meaning of the song Letto based on majas with the implementation of the TGT model. Keywords: Team Game Tournament (TGT), experimental class, control class, student response